2014
DOI: 10.1002/pc.23232
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of flexible polymeric shielding materials for soft gamma rays: Physicomechanical and attenuation characteristics of radiation crosslinked polydimethylsiloxane/Bi2O3 composites

Abstract: Flexible lead‐free high energy radiation shielding material was developed through internal compounding. Polymer‐filler interaction, crosslinking density, specific gravity, physicomechanical characteristics, percentage attenuation, and thermal stability of the crosslinked composites were estimated. It was found that even at very high filler loading composites can be crosslinked; however, the crosslinking density was composition dependent and was highest in 10–50 wt% loading range at 100 kGy and 200 kGy. The Nie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The necessity of lightweight radiation attenuating material is well agreeable from the Fukushima disaster in 2011 32 . The composite with the use of high 'z' metal filler in a EPDM matrix can increase the radiation‐attenuation and physico‐mechanical properties of the material 33 . The choice of suitable fillers and their composition can alter the final characteristics of the composite 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The necessity of lightweight radiation attenuating material is well agreeable from the Fukushima disaster in 2011 32 . The composite with the use of high 'z' metal filler in a EPDM matrix can increase the radiation‐attenuation and physico‐mechanical properties of the material 33 . The choice of suitable fillers and their composition can alter the final characteristics of the composite 34 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these demerits of lead, researchers are in ease to fabricate a lead free shielding material, which is light weight and effective in absorbing high energy radiations. Research efforts is enhancing day by day, such that, a few studies have been reported on polymer composite radiation shields over the globe, whereas in India, studies are being carried out mainly on glass based radiation shields, and a very few on polymers composites . The chief advantage of using polymers as a matrix is the low cost, easy processability, good chemical resistance, low specific gravity and light weight.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these are usually stiff with high moduli making it difficult to process them in wearable form. Flexible shielding materials are advantageous for the personnel working in nuclear fuel processing industry, nuclear reactors, nuclear waste management, radiopharmaceutical industry, and space explorations where radiation exposure is unavoidable 12 . Furthermore, to comply with today's requirement of greener and sustainable technologies, it is imperative to switch over from synthetic plastics to naturally available biodegradable polymers.…”
Section: Introductionmentioning
confidence: 99%